Daytime Exposure to Short- and Medium-Wavelength Light Did Not Improve Alertness and Neurobehavioral Performance. (October 2016) - Segal, Ahuva Y.; Sletten, Tracey L.; Flynn-Evans, Erin E.; Lockley, Steven W.; Rajaratnam, Shantha M. W.
While previous studies have demonstrated short-wavelength sensitivity to the acute alerting effects of light during the biological night, fewer studies have assessed the alerting effect of light during the daytime. This study assessed the wavelength-dependent sensitivity of the acute alerting effects of daytime light exposure following chronic sleep restriction in 60 young adults (29 men, 31 women; 22.5 ± 3.1 mean ± SD years). Participants were restricted to 5 h time in bed the night before laboratory admission and 3 h time in bed in the laboratory, aligned by wake time. Participants were randomized for exposure to 3 h total of either narrowband blue (λmax 458-480 nm, n = 23) or green light (λmax 551-555 nm, n = 25) of equal photon densities (2.8-8.4 × 10 13 photons/cm 2 /sec), beginning 3.25 h after waking, and compared with a darkness control (0 lux, n = 12). Subjective sleepiness (Karolinska Sleepiness Scale), sustained attention (auditory Psychomotor Vigilance Task), mood (Profile of Mood States Bi-Polar form), working memory (2-back task), selective attention (Stroop task), and polysomnographic and ocular sleepiness measures (Optalert) were assessed prior to, during, and after light exposure. We found no significant effect of light wavelength on these measures, with the exception of a single mood subscale. Further research is needed to optimize the characteristics of lighting systems to induce alerting effects during the daytime, taking into account potential interactions between homeostatic sleep pressure, circadian phase, and light responsiveness.